Detection of Volatile Organic Compounds by Weight-Detectable Sensors coated with Metal-Organic Frameworks - Yamagiwa, Hiroki (Nature Publishing Group, 2014)
Detection of volatile organic compounds (VOCs) using weight-detectable quartz microbalance and silicon-based microcantilever sensors coated with crystalline metal-organic framework (MOF) thin films is described in this paper. The thin films of two MOFs were grown from COOH-terminated self-assembled monolayers onto the gold electrodes of sensor platforms. The MOF layers worked as the effective concentrators of VOC gases, and the adsorption/desorption processes of the VOCs could be monitored by the frequency changes of weight-detectable sensors. Moreover, the MOF layers provided VOC sensing selectivity to the weight-detectable sensors through the size-selective adsorption of the VOCs within the regulated nanospace of the MOFs.